2018
DOI: 10.1111/imb.12382
|View full text |Cite
|
Sign up to set email alerts
|

Thioester‐containing proteins in the tsetse fly (Glossina) and their response to trypanosome infection

Abstract: Thioester‐containing proteins (TEPs) are conserved proteins with a role in innate immune immunity. In the current study, we characterized the TEP family in the genome of six tsetse fly species (Glossina spp.). Tsetse flies are the biological vectors of several African trypanosomes, which cause sleeping sickness in humans or nagana in livestock. The analysis of the tsetse TEP sequences revealed information about their structure, evolutionary relationships and expression profiles under both normal and trypanosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 60 publications
(85 reference statements)
0
7
0
Order By: Relevance
“…BgTEP3 harbors a single nucleotide mutation in this site leading to the replacement of the cysteine residue to a serine residue, but the Gln-moiety of the thioester is preserved. Such replacement of the cysteine residue by a serine was also reported for tsetse fly TEP2, an iTEP of which the expression is particularly up-regulated in the salivary gland following Trypanosoma brucei infection [69]. The replacement of cysteine residue in the thioester site was also evidenced for chicken ovostatin [70], without alteration of its proteinase-inhibitor activity [71].…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…BgTEP3 harbors a single nucleotide mutation in this site leading to the replacement of the cysteine residue to a serine residue, but the Gln-moiety of the thioester is preserved. Such replacement of the cysteine residue by a serine was also reported for tsetse fly TEP2, an iTEP of which the expression is particularly up-regulated in the salivary gland following Trypanosoma brucei infection [69]. The replacement of cysteine residue in the thioester site was also evidenced for chicken ovostatin [70], without alteration of its proteinase-inhibitor activity [71].…”
Section: Discussionmentioning
confidence: 68%
“…Genes 2020, 11, 69 6 of 16 transcripts corresponding to incomplete BgC3-2 cDNA was previously identified from the B. glabrata genome publication [49]. BgA2M also clustered with the A2M members from other mollusks.…”
Section: Bgtep Protein Features Analysismentioning
confidence: 99%
“…Some genes have been demonstrated to have functions in both immunity and reproduction in various animals (Li et al, 2001;Loongyai et al, 2007;Cao et al, 2010;Pompon & Levashina, 2015). For example, thioestercontaining protein 1 (TEP1) is a critical immune factor that mediates insect resistance to a wide range of pathogens (Oliveira et al, 2012;Matetovici & van Den Abbeele, 2018). However, it was reported that TEP1 had a new role in male fertility in the mosquito Anopheles gambiae through binding to, and removal of the aberrant sperm to preserve high fertility rates (Pompon & Levashina, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Thioester-containing complement-like proteins and Nimrod family proteins are immune factors that influence the migration of hemocytes to the heart of mosquitoes and fruit flies ( 11 , 12 , 16 , 30 ). Both of these protein families are encoded in the genomes of diverse insects ( 31 , 32 ), so their roles in heart-associated responses likely extend beyond Diptera. In addition, a collagen protein that is part of the cardiac extracellular matrix, called Pericardin, facilitates the aggregation of hemocytes on the heart of fruit flies ( 13 ).…”
Section: Discussionmentioning
confidence: 99%